2009
DOI: 10.1007/s00122-009-0965-x
|View full text |Cite
|
Sign up to set email alerts
|

QTL, additive and epistatic effects for SCN resistance in PI 437654

Abstract: PI 437654 is a unique accession because of its resistance to nearly all HG types (races) of soybean cyst nematode (Heterodera glycines Ichinohe; SCN). Objectives of this study were to confirm and refine the locations and gene action associated with SCN resistance previously discovered in PI 437654, and to identify new QTLs that may have been missed because of low coverage with genetic markers used in previous studies. Using 205 F(7:9) RILs and 276 SSR and AFLP molecular markers covering 2,406.5 cM of 20 linkag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
143
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(165 citation statements)
references
References 56 publications
16
143
0
5
Order By: Relevance
“…However, we discovered the near identity of PI 437654 Rhg1 copy number and sequence to other, less broadly resistant Rhg1 low-copy soybean lines. Although Rhg1 makes one of the strongest contributions to PI 437654-derived resistance (Webb, 2012), the present finding reemphasizes the importance of identifying and cloning additional SCN resistance quantitative trait loci from PI 437654 (Wu et al, 2009). …”
Section: Discussionmentioning
confidence: 61%
“…However, we discovered the near identity of PI 437654 Rhg1 copy number and sequence to other, less broadly resistant Rhg1 low-copy soybean lines. Although Rhg1 makes one of the strongest contributions to PI 437654-derived resistance (Webb, 2012), the present finding reemphasizes the importance of identifying and cloning additional SCN resistance quantitative trait loci from PI 437654 (Wu et al, 2009). …”
Section: Discussionmentioning
confidence: 61%
“…Yu et al (2016) showed that rhg1-a alone may confer some level of resistance in crosses using PI 437654, a PI with a similar copy number (three copies) to that in cv Forrest. PI 437654 has a similar epistatic relationship between rhg1 and Rhg4 in conferring resistance to SCN (Wu et al, 2009). Unlike cv Forrest, PI 437654 is resistant to multiple SCN HG types, and although its resistance is poorly understood, it likely involves other unknown loci in addition to rhg1 and Rhg4.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the mapping of only two QTL from PI 88788, many resistance QTL have been mapped from PI 437654 (Webb et al, 1995;Wu et al, 2009). This may explain why PI 437654 is resistant to more HG (Heterodera glycines Ichinohe) types than PI 88788 (Anand et al, 1988;Diers et al, 1997;Niblack et al, 2002).…”
mentioning
confidence: 99%